Art therapy for anxiety, depression, and fatigue in females with breast cancer: A systematic review. Issue 1 (2nd January 2019) - Tang, Yong; Fu, Fang; Gao, Hua; Shen, Li; Chi, Iris; Bai, Zhenggang
Abstract: This systematic review employed a meta-analysis to examine the effectiveness of art therapy for treating anxiety, depression, and fatigue in female patients with breast cancer, the most prevalent cancer and the most common cause of cancer-related mortality among women worldwide. The review included nine original studies and analyzed data from a total of 754 patients. Data extraction and quality assessment were conducted by two independent reviewers. In total, 1, 466 articles were retrieved. We excluded studies in which the participant, interventions, and study design did not satisfy the inclusion criteria, leaving nine articles for analysis, The Cochrane risk of bias assessment tools were used for quality evaluation. The analysis revealed a significant difference in treatment outcomes between patients who received art therapy and those who did not (SMD = –0.48, 95%CI [–0.75, –0.21, p  = 0.0005]). The review provides initial evidence to suggest that art therapy benefits female breast cancer patients with respect to the treatment of anxiety, depression, and fatigue. However, additional and better-quality studies must be conducted, particularly with larger sample sizes, greater specificity of the design of trials and interventions, and a longer follow-up duration.